Incidence of atrial fibrillation. A comprehensive nationwide analysis in Finland. (14th October 2021) - Lehto, M; Haukka, J; Halminen, O; Mustonen, P; Putaala, J; Linna, M; Kinnunen, J; Kouki, E; Luojus, A; Tiili, P; Itainen-Stromberg, S; Aro, A; et al.
Abstract: Introduction: Atrial fibrillation (AF) is a chronic condition, and once diagnosed, most of the patients need life-long treatment for AF; rate and rhythm control for symptom relief and oral anticoagulation to mitigate the associated risk of stroke. Incidence of AF is strongly associated with age, and with longer life-expectancy the number of AF patients is worldwide rapidly increasing. Purpose: The FinACAF study is a nationwide registry study including all AF patients searched from comprehensive national health care registers. To our knowledge, FinACAF is the first nationwide study including both primary, secondary, and tertiary health care register data. The aim of this study was to assess the incidence of new-onset AF in unselected nationwide population in Finland. Methods: In the FinACAF study we gathered data (hospitalizations, outpatient specialist and primary health care visits, and drug reimbursement) from all national health care registers to identify new-onset AF patients from 01st January 2004 to 31st December 2018. To minimize the risk of misclassification, we considered a patient to have incident AF only if the new-onset AF diagnosis emerged after 1st January 2007 allowing at least three years of registration in Finnish health care registers without diagnosis of AF. Furthermore, patients with warfarin prescriptions during 2004–2006 were excluded. Raw incidence rates (1/100 000) were calculated using the total number of incident AF cases during a given year as numerator, and the total number of Finnish population free of AF on the last day of that year as denominator. The age-standardized incidence rates (1/100 000) were calculated using the total number of new-onset AF cases per year compared to the Nordic population free of AF age distribution. Results: In total, 411 080 patients with the diagnosis of AF were documented during 2004–2018 in Finland, and the number of new-onset AF patients during 2007–2018 was 256 323. The incidence of AF in relation to age is shown in the Figure 1, and the increasing incidence with advancing age is outstandingly seen. Incidence of AF was more than 2000/100 000 in the population 80 years or older. The incidence of new-onset AF in the whole Finnish population increased during the study period from 330/100 000 and peaked to 456/100 000 in 2018. However, after adjustment for age, the age-adjusted AF incidence remained unchanged during 2007–2018 (Figure 2), but an obvious leap in the incidence emerged during 2011–2013 when the national primary care register was established. Conclusions: In 2018 the incidence of AF per the whole population was 456/100 000. Based on very novel data and including all the known, diagnosed AF patients in Finland, this is the highest reported incidence rate of AF. Incidence of AF is strongly age-dependent, but the age-standardized incidence was not significantly changed from 2007 to 2018. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): Helsinki and Uusimaa Hospital District research fundThe Finnish Foundation for Cardiovascular Research